2017
DOI: 10.1007/s00248-017-1092-x
|View full text |Cite
|
Sign up to set email alerts
|

Accessing the Hidden Microbial Diversity of Aphids: an Illustration of How Culture-Dependent Methods Can Be Used to Decipher the Insect Microbiota

Abstract: Microorganism communities that live inside insects can play critical roles in host development, nutrition, immunity, physiology, and behavior. Over the past decade, high-throughput sequencing reveals the extraordinary microbial diversity associated with various insect species and provides information independent of our ability to culture these microbes. However, their cultivation in the laboratory remains crucial for a deep understanding of their physiology and the roles they play in host insects. Aphids are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 83 publications
3
32
0
Order By: Relevance
“…The aphid-associated bacterium S. symbiotica has typically been described to be a strict endosymbiont, but the discovery of cultivable strains that are potentially capable of growing outside aphid hosts shows a different aspect of this symbiont species and raises questions about its associated biological effects, as well as the nature and the durability of the associations in which it is involved. These strains have been isolated from Aphis species but have not been clearly localized in their original hosts (36,37). Nevertheless, a new field study revealed that these cultivable strains belong to the same clade as other S. symbiotica strains that reside in the aphid gut harvested in the field (38), suggesting that they would derive , and weight of emerged parasitoids (C).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aphid-associated bacterium S. symbiotica has typically been described to be a strict endosymbiont, but the discovery of cultivable strains that are potentially capable of growing outside aphid hosts shows a different aspect of this symbiont species and raises questions about its associated biological effects, as well as the nature and the durability of the associations in which it is involved. These strains have been isolated from Aphis species but have not been clearly localized in their original hosts (36,37). Nevertheless, a new field study revealed that these cultivable strains belong to the same clade as other S. symbiotica strains that reside in the aphid gut harvested in the field (38), suggesting that they would derive , and weight of emerged parasitoids (C).…”
Section: Discussionmentioning
confidence: 99%
“…Cultivable S. symbiotica strain CWBI-2.3 T (S1ϩ), isolated from a field-collected A. fabae aphid (36,39), was used in this study. In addition, we isolated two novel strains of S. symbiotica as described previously (36,37): strain 24.1 (S2ϩ) from a field-collected A. fabae aphid and strain Apa8 A1 (S3ϩ) from an Aphis passeriniana aphid collected in Tunisia. These strains, which had a free-living capacity, were preserved in frozen stocks at Ϫ80°C and cultured at 20°C in 863 medium (1% yeast extract, 1% casein peptone, 1% glucose) as described previously (36).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We report here the draft genome sequences of two S. symbiotica strains displaying free-living capacities, namely, strain 24.1, previously isolated from the black bean aphid Aphis fabae, and strain Apa8A1, previously isolated from the sage aphid Aphis passeriniana (7). Bacterial cultures were started from single colonies and grown in 863 medium at 20°C (6).…”
mentioning
confidence: 99%
“…In the pea aphid Acyrthosiphon pisum (subfamily Aphidinae), S. symbiotica includes intracellular strains of a facultative nature showing moderately reduced genome sizes (3,(20)(21)(22). In addition to co-obligate and facultative strains, S. symbiotica also includes strains capable of growing independently from their host aphid on an artificial rich medium (6,7). The genomic features of the strain CWBI-2.3 T , isolated from A. fabae, suggest that it may represent a missing link in the evolution of a free-living lifestyle toward a host-dependent lifestyle (1, 2, 6, 7).…”
mentioning
confidence: 99%